Current status and future perspectives of lithium metal batteries - Varzi, Alberto; Thanner, Katharina; Scipioni, Roberto; Di Lecce, Daniele; Hassoun, Jusef; Doerfler, Susanne; Altheus, Holger; Kaskel, Stefan; Prehal, Christian; Freunberger, Stefan A. (Journal of Power Sources, 2020)
With the lithium-ion technology approaching its intrinsic limit with graphite-based anodes, Li metal is recently receiving renewed interest from the battery community as potential high capacity anode for next-generation rechargeable batteries. In this focus paper, we review the main advances in this field since the first attempts in the mid-1970s. Strategies for enabling reversible cycling and avoiding dendrite growth are thoroughly discussed, including specific applications in all-solid-state (inorganic and polymeric), Lithium–Sulfur (Li–S) and Lithium-O2 (air) batteries. A particular attention is paid to recent developments of these battery technologies and their current state with respect to the 2030 targets of the EU Integrated Strategic Energy Technology Plan (SET-Plan) Action 7.
CRIS-Team Scopus Importer:2022-04-14
Keywords: All-solid-state; Battery; Lithium metal; Lithium-air; Lithium–sulfur